Paradoxes of temporality in avant-gard (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This text is aimed to rethink the possibilities of contemporary political art. Consequently, we will use the dilemmatic aspects proposed by Jacques Rancière in his book The Emancipated Spectator, that is, the outdated frameworks developed by political art. Nevertheless, we will also take distance from Ranciere’s genealogical work through which he assumes that the persistence of a certain theological conception of time −one that can be observed both in modernity and avant-garde− is a symptomatic aspect that contemporary art would later repeat. Our strategy consists of pointing out that is possible to create a narrative of avant-garde that assumes a different conception of temporality. If so, the concept of avant-garde would come closer to the notion of aesthetic regime proposed by Rancière, and it could also be still relevant to conceive the dilemmas of contemporary political art.